Kemampuan Literasi Matematika Dalam Memecahkan Masalah Matematika Pada Siswa Kelas VIII SMP Negeri 2 Woha - Ramdani, Nurlailatun; Fatimah, Nunung (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to describe the ability of mathematical literacy in solving mathematical problems in class VIII SMP Negeri 2 Woha. This research is a qualitative research using a descriptive approach. Data collection was carried out on class VIII students of SMP Negeri 2 Woha in the 2020/2021 academic year and the selection of subjects was based on the level of students' mathematical abilities. The research instrument used was a matter of students' mathematical literacy skills in solving mathematical problems. Data collection techniques were carried out by tests and interviews. The results obtained from students with high categories are able to carry out several stages of the student literacy process in solving mathematical problems well in the section formulating, applying concepts, facts, procedures, and reasoning but in the problem section, application, problem finding and drawing conclusions students have not maximum work and explain when to interview